The impact of price increases on consumer behavior of marketing students at Pamantasan ng Lungsod ng Maynila Basis for evaluating pricing strategies of business - Acopio, Angel Shyke D., Acuman, Mariah Paula B., Alcones, Trixie Maureen Y., Balisi, Joelyn V., Llacuna, Kyle Voughn K., Rivera, Dannyn Kaarina C., Salcedo, Rein Russel R., Venus, Enzo Bludymier Kroyd H. 4 0 16; 5
Abstract This study aimed to determine the impact of price increases on the consumer behavior of the marketing students in Pamantasan ng Lungsod ng Maynila, use this as the basis for evaluating the pricing strategies of businesses, and analyze the effects of pricing strategies on businesses using the Unified Theory of Pricing. The researchers utilized a quantitative approach, specifically employing cross - sectional study. They conducted a convenience sampling of 154 marketing student respondents from Pamantasan ng Lungsod ng Maynila who were surveyed online using MS Forms. The findings indicated that the most common pricing strategy encountered by the PLM marketing students was penetration pricing and high-low pricing, with the help of the associated promotions on these pricing strategies. Additionally, the study revealed the factors that affect consumer behavior. The data gathered also highlighted that price sensitivity impacts consumer purchasing decisions, because of the promotional strategies mentioned. The study would be valuable for future researchers since it conducted a study about pricing strategies and consumer behavior. Keywords: The Unified Theory of Pricing, Pricing Strategies, Consumer Behavior.
Business Research: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2